Prosedur Penerjemahan Unsur Satire Terkait Eksil Indonesia dalam Video Dokumentasi CNA Insider - Salma Arezha; Lusianti Dwi Cahyani; Winda Aprilia Maharani (Universitas Sebelas Maret, 2025)
In the video “Indonesia's Exiles: Too Late to Return Home?” by CNA Insider, a translation phenomenon is found. Differences in social and political conditions in expressing satire can be an obstacle in translation, making the selection of translation methods and procedures more complicated. This study aims to reveal the satire elements and translation procedures in the video entitled “Indonesia's Exiles: Too Late to Return Home?”. This study is a translation research with Indonesian BSu and English BSa. The data in this study are taken from CNA Insider's YouTube video. The research used descriptive qualitative method with simak and catat taking techniques. As a result, three irony, six cynicism, and 15 sarcasm data were found to dominate the video. Furthermore, a combined direct and oblique translation method was also found. However, oblique is more dominant due to the complexity of the different social and political conditions of Indonesia in 1965. Three data of literal translation procedure, two data of calque, five data of adaptation, three data of transposition, one data of equivalence, and ten data of modulation were found. Modulation dominates because of the demand to clarify the SVO to distinguish the perpetrators and sufferers of human rights violations.